Efficacy of Axitinib After Nivolumab Failure in Metastatic Renal Cell Carcinoma - ISHIHARA, HIROKI (In Vivo, 2020)
Background/Aim: Whether molecular-targeted therapy, particularly axitinib, is effective after failure of immune checkpoint inhibitors in metastatic renal cell carcinoma (mRCC) remains unclear. Here, we evaluated the therapeutic effect of axitinib as a third-line therapy following second-line nivolumab monotherapy for mRCC. Patients and Methods: Data from patients treated with axitinib as a third-line therapy after failure of first-line tyrosine kinase inhibitor (TKI) and second-line nivolumab monotherapy were reviewed. The progression-free survival (PFS), overall survival (OS), and objective response rate during axitinib therapy were retrospectively evaluated. Tumor responses were assessed according to the Response Evaluation Criteria in Solid Tumors version 1.1. Results: Seventeen patients were treated with third-line axitinib after failure of prior TKI and nivolumab. During a median follow-up of 8.15 months, eight (47.1%) and three (17.6%) patients showed disease progression and died, respectively. The median PFS was 12.8 months [95% confidence interval=(CI)4.08-21.7], the 1-year PFS rate was 51.3%, and the 1-year OS rate was 71.6%. The median magnitude of maximum changes of targeted lesions from baseline was –11.9% (95%CI=–36.1-0.44%). The objective response rate and disease control rates were 29.4% (n=5) and 94.1% (n=16), respectively. Univariate analysis for PFS showed a shorter PFS in patients with non-clear cell histopathological types or those with liver metastases (p-Value<0.0001 for both). Conclusion: Axitinib as a third-line therapy showed reasonable therapeutic efficacy after the failure of first-line TKI and second-line nivolumab monotherapy for mRCC. Further studies are needed to confirm our findings.